University Brand Development Model and Communication Strategy to Create a Competitive Advantage of Silpakorn University, Thailand - Klangrahad, Chombhak (วารสารวิจัยราชภัฏธนบุรี รับใช้สังคม, 2026)
This research addresses Silpakorn University's challenge of reconciling its historical 'art school' identity with its modern, multi-disciplinary status. A mixed-method, convergent parallel design was employed. The qualitative stream involved semi-structured interviews with 7 key university staff, while the quantitative stream surveyed 684 undergraduate students to test a proposed model grounded in Stimulus-Organism-Response (S-O-R) theory. Data were analyzed using thematic analysis and Structural Equation Modeling (SEM). The model reveals that Brand Image is the most powerful predictor of student Brand Advocacy, significantly outweighing Brand Awareness. Branding activities like student Interaction and perceived Trendiness were the most influential stimuli, shaping this positive image indirectly. The study concludes that fostering brand advocacy requires meticulously cultivating a strong brand image through a holistic, student-centric approach that harmonizes the university's legacy with its modern identity.